Pengembangan Aplikasi Mobile Android SIMIPA untuk Modul Dosen Fitur Rekapitulasi, Kemajuan Skripsi, Validasi Tema, dan Validasi Seminar Menggunakan Metode Scrum - Ardiansyah; Didik Kurniawan; Dwi Sakethi; Megi Aji Pangestu (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
Lectures are a means of improving students to be able to explore more abilities possessed by each individual. One of the factors that are closely related to the increase in students is lecturers or teaching staff. Lecturers who are at the Faculty of Mathematics and Natural Sciences at the University of Lampung themselves in supervising the improvement of each student have been assisted by a web-based system, namely the MIPA information system. This supervision can be improved by utilizing technological advances, one of which is by developing android-based applications. The development of the Android-based SIMIPA application, especially for lecturers, can improve lecturer supervision for each student guidance at the Faculty of Mathematics and Natural Sciences (FMIPA) at the University of Lampung. The development of this application itself uses one type of Agile Development method, namely the Scrum method and is developed based on the backlog product that has been determined. The result of this research is the development of the SIMIPA application for android-based lecturers successfully developed using the Scrum method. The success of this development shown from the results of testing using the Black box testing method which states the overall functionality the SIMIPA application fits well.